2020
DOI: 10.1111/nep.13743
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory features of female Gitelman syndrome and the pregnancy outcomes in a Chinese cohort

Abstract: Aim Gitelman syndrome (GS) is a rare inherited salt‐losing renal tubulopathy. Data on clinical features and the pregnancy outcome for female GS patients in a large cohort are lacking. The study was aimed to explore the phenotype and pregnant issue for female GS patients. Methods GS cases from the National Rare Diseases Registry System of China (NRSC) were collected, and detailed clinical, laboratory and genetic data were analysed. Articles on pregnancy in GS were also systemically reviewed. Results A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Although GS in pregnancy is reported, severe cases requiring continuous intravenous electrolyte repletion are rare, with little guidance regarding anesthesia care [5,[7][8]. In a recently published cohort study of 43 patients, only three required IV electrolyte supplementation [3]. While parturients in this cohort had relatively mild disease and subsequent uneventful pregnancies, adverse maternal and fetal outcomes among GS patients have been reported.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Although GS in pregnancy is reported, severe cases requiring continuous intravenous electrolyte repletion are rare, with little guidance regarding anesthesia care [5,[7][8]. In a recently published cohort study of 43 patients, only three required IV electrolyte supplementation [3]. While parturients in this cohort had relatively mild disease and subsequent uneventful pregnancies, adverse maternal and fetal outcomes among GS patients have been reported.…”
Section: Discussionmentioning
confidence: 98%
“…While GS has wide phenotypic variation, common symptoms include muscle cramping, orthostatic hypotension, palpitations, weakness, and fatigue [3]. Management includes liberal salt intake as well as potassium and magnesium supplementation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study demonstrated an efficacy greater than 85% in finding the causal BS mutations [ 76 ]. For GS, the diagnostic efficacy is lower, around 62% [ 5 , 136 , 137 , 138 , 139 ], and a considerable number of clinical-diagnosed patients carries only one mutation (around 25%) [ 136 , 137 , 138 , 139 ]. In both scenarios, it is recommended to carry out a study of carriers of the variants identified in the parents, in order to determine that each variant is located in different copies of the gene.…”
Section: Diagnostic Approachesmentioning
confidence: 99%